2022
DOI: 10.1002/admi.202200369
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Nanostructured Bimetallic Au–Ag Films for Enantiomeric Discrimination

Abstract: circular dichroism, [3] electronic circular dichroism [4] and Raman optical activity, [5] has been used in both quantitative analysis and absolute configuration study of the enantiomers. However, the feasibility of enantiomeric discrimination by chiral chromatography strongly depends on molecular polarity and mass of enantiomers, which narrows applicable conditions and molecules for each chiral column. Chiral spectroscopy is impossible to be used for enantioselective discrimination of racemates or chiral mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Therefore, based on the chirality-induced spin selectivity theory, the mechanism of SERS-ChA C–E can be deduced (Figure b). (i) Anisotropic photomagnetic fields were generated by antipodal CNAFs owing to chirality-induced spin selectivity of CNAFs under laser irradiation, resulting in effective spin polarization in chiral structures. , The strength of spin selectivity depends on the length of the path through which the electron passes due to the selectivity of the chiral potential for electrons . (ii) The selective SPC between CNAFs and enantiomers results in the selective enhancement of the magnetic fields of CNAFs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on the chirality-induced spin selectivity theory, the mechanism of SERS-ChA C–E can be deduced (Figure b). (i) Anisotropic photomagnetic fields were generated by antipodal CNAFs owing to chirality-induced spin selectivity of CNAFs under laser irradiation, resulting in effective spin polarization in chiral structures. , The strength of spin selectivity depends on the length of the path through which the electron passes due to the selectivity of the chiral potential for electrons . (ii) The selective SPC between CNAFs and enantiomers results in the selective enhancement of the magnetic fields of CNAFs .…”
Section: Resultsmentioning
confidence: 99%
“…Chirality is known as the geometric asymmetry of a large group of molecules with a non-superposable mirror image, either left- or right-handedness. , Due to the homochirality in biosystems that are very sensitive to the chiral orientation of compounds, enantiomeric discrimination is of vital importance in both pharmaceutical fields and investigating life activities. , For enantiomeric discrimination, chiral response, which depends on the handedness matching and mismatching between the enantiomers and chiral structures, is often employed. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, more chiral hybrid plasmonic materials have been designed and used as excellent substrates for significantly amplifying the molecular vibrational signal, particularly for SERS. 79,130…”
Section: Emerging Applications Of Multicomponent Chiral Plasmonic Hyb...mentioning
confidence: 99%
“…4c ). 79 SEM and TEM images revealed that the films grew perpendicular to the substrate, forming polycrystalline Boerdijk–Coxeter–Bernal (BCB) four-fold helical structures composed of AuAg alloy. CD diffuse reflectance spectra indicated chiroptical signals at 545 nm for the entire substrate, exhibiting mirror-image symmetry influenced by the chirality of the molecules.…”
Section: Synthesis Of Multicomponent Chiral Plasmonic Hybrid Nanomate...mentioning
confidence: 99%
“…With the rapid development of chiral plasmonic nanostructures/superstructures, further study of their chirality-related optical properties become possible, such as chiral-field-steered emissions and surface-enhanced Raman scattering (SERS) [ 74 , 75 ], photothermal chirality [ 76 , 77 ], and chiral photoluminescence (PL) from chiral structures themselves [ 78 , 79 ] to name a few ( Figure 3 ). Using the combination of chiral plasmonic antenna and monolayer transition metal dichalcogenides, Lu et al demonstrated the huge modulation of the valley-polarized PL of monolayer MoS 2 located in a nanogap of two AuNRs in a chiral configuration ( Figure 3 a) [ 78 ].…”
Section: Optical Properties Of Chiral Plasmonic Nanomaterialsmentioning
confidence: 99%